Debate: This Thing Called Discourse: What difference a discourse makes - du Preez, Peter (PINS-Psychology in Society, 2026)
Review Levett, A, Kottler, A, Burman, E & Parker, I (eds) (1997) Culture, power and difference: Discourse analysis in South Africa. London & New Jersey: Zed Books; Cape Town: University of Cape Town Press. ISBN 1-919713-08-5. Pbk, 210 pages. Perhaps the best way to start this review is to examine the first and last chapters, written by the editors and providing the frame of the book. What's discourse analysis about? Briefly, it's about the performances of power as revealed in texts. These performances get interpreted in new performances of power by discourse analysts.